Micropropagation of Pogostemon paniculatus - Godbole, Manoj; K N, Vanya; H D, Lenifer; Y, Amrutha; K, Shruthi; S, Sujay K (Asian Journal of Pharmaceutical Research and Development, 2022)
Plant regeneration potential from node & leaf explants of Pogostemon paniculatus through direct shoot proliferation was studied on Murashige and Skoog medium supplemented with various concentrations of cytokinins & auxins. As the seed germinability of the plant is low in vitro, we have tried these explants for micropropagation. Among different concentrations of individual hormones tested for nodal explants, benzylaminopurine (BAP) at 5µM & kinetin (Kn) at 0.5µM showed 4 & 2 mean number of shoots/explant respectively & combination of Kn (0.5 µM) + BAP (1.5 µM) showed 15 mean number of shoots/explant. For leaf explant combination of Kn (0.5 µM) + BAP (1.5 µM) showed 20 mean number of shoots/explant. Other hormones tested at all concentrations showed callus formation without the shoot development. Roots were established on the isolated shoots on naphthaleneacetic acid (NAA) at 0.25µM. Rooted plants were acclimatized. This is the first report of Pogostemon paniculatus micropropagation.